You don't know what it's like : the lived experience of drug dependence : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Williams, Margaret A. Adams (Massey University, 2002)
This phenomenological study describes the lived experience of drug dependence and relates the understanding gained from this description to drug dependence practice. The participants in this study were 25 adults who had a recognized dependence on one or more psychoactive drugs as identified by the DSM IV criteria of substance dependence. Over a period of eight months the participants were interviewed about their lived experience of drug dependence and the effects of drug dependence on their everyday lives. Interviews were audiotaped and transcribed into text They were then analyzed and interpreted hermeneutically against a background of Heideggerian philosophy. Drawing upon Heideggerian concepts with great relevance to this study, three related themes emerged to describe the lived experience of drug dependence: Becoming and being drug dependent - the journey; Being with others; and Being with care. These themes point to the nature of drug dependence and the extent to which the experience affects the whole of the participants' Being-in-the-world. Drug dependence was viewed as a powerful life experience that can be likened to a journey, one that the participants would go to any lengths just to carry on with. The longer they stayed on the journey the more drug dependence affected their whole Being-in-the-world in terms of feeling and being different, both physically and psychically. Through being drug dependent the participants were found to inhabit two worlds, a We world and a Them world. In both worlds the participants found themselves alongside others with whom they related. Such relationships were found to be significant in that not only did being with others impact upon the participants' drug dependence, the participants' drug dependence also impacted upon their being with others. Through their choices and actions each of the participants revealed what mattered to them, that which they were concerned with, and cared for. Encompassed within that which they care for, their Being with care, is the stand each is taking on their own Being in the world, their choice of self, and the meaning they give to their existence. For the participants, the experiential sharing of their lived experience of drug dependence not only enabled them to reflect on their own Being and to find meaning in their lives, but also to provide important insights into the lived experience of drug dependence for all those, including health care professionals, who interact with drug dependent people. Also illustrated in this study is the importance of acknowledging drug dependent persons as valuable human beings and of understanding their needs for the provision of effective care in drug dependence practice. Finally, the use of a hermeneutic data analysis approach has shown the relevance of this method for the unfoldment of new understandings of the human experience of drug dependence.
Keywords: Drug addicts; Personal narratives; Biography; Psychology; New Zealand; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology